EKSISTENSI SULAMAN KARAWO DALAM MENUNJANG PARIWISATA GORONTALO - Srilian Laxmiwaty Dai (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2019)
The objective of this article is to figure out the obstacles of Karawo comodification existence as Gorontalo traditional souvenir and also to formulate the solutions of those identified obstacles. Besides that, this article also aimed to describe the role of Karawo which is very important in tourism industry. This article analyzed by descriptive qualitative with the existance theory. The result that has been found by this article is the obstacles of Karawo existence as Gorontalo traditional souvenir in supporting tourism activities is the producers perspective, they stated that embroidering is complicated and also need a long procces about two till three months to produce a piece of Karawo with a little demand. It is the reason why the price is expensive. It becomes more complicated because of the less people interested to be an Karawo embroider. The solution formulated Based on obstacles firstly, improving the awareness of the Gorontalists young generation for loving their culture. Secondly encouradge the young generation to creatively and innovatively create a technology to replace the human as embroider with the big number of product produced. Tourism is the cultural preservation so that Karawo existence in tourism needs more attention from all stakeholders. Not only attention, but also the stakeholders need to be cooperative in implementing the solutions offered.